Right Breast Metaplastic Carcinoma with Chondroid Diff erentiation (Chondrosarcoma) - Alya S. Binmahfouz (Journal of King Abdulaziz University: Medical Sciences, 2023)
Metaplastic breast cancer is rare, representing < 5% of breast cancer (only eight cases have been reported so far). We present here a 42-year-old female complaining of a painless lump in the right breast for the previous two months. Physical examination revealed a palpable mass. Lumpectomy was performed and histopathologic examination revealed metaplastic breast carcinoma with foci of chondrosarcoma. The patient received adjuvant radiation therapy and chemotherapy and is currently following up as an outpatient. We also discuss diff erent imaging diagnostic features of this specifi c type of breast cancer using mammography, ultrasonography, and magnetic resonance imaging.